Model Pembelajaran Discovery Learning Berbantuan PhET Simulation untuk Meningkatkan Hasil Belajar Materi Energi - Sumarno, Salsabla Maulani; Hartanto, Theo Jhoni; Dinata, Pri Ariadi Cahya (Jurnal Ilmiah Kanderang Tingang, 2024)
Understanding the concept of energy is a crucial aspect of science education, as it serves as the foundation for comprehending various natural phenomena and processes around us. However, the energy concept comprehension of Class VIII-A students at SMP Negeri 13 Palangka Raya remains low due to their lack of active participation during lessons and the unappealing media used in teaching. This low understanding results in poor learning outcomes. To address this issue, this study employs the discovery learning model supported by PhET Simulation media. The aim of this research is to improve learning outcomes on the topic of energy. The study was conducted in two cycles using Classroom Action Research (CAR). Each cycle involved four stages: planning, action, observation, and reflection. Data were collected from 18 students in Class VIII-A of SMP Negeri 13 Palangka Raya during the 2023/2024 academic year and from colleagues. Data collection methods included teacher activity observation sheets and student learning outcome tests, which were then analyzed descriptively. The results showed an increase in the students' average scores from 87.06 in Cycle I to 87.22 in Cycle II, with an improvement in classical mastery from 82.35% to 83.33%. It can be concluded that the use of the discovery learning model supported by PhET Simulation media on the topic of energy successfully enhanced the learning outcomes of Class VIII-A students at SMP Negeri 13 Palangka Raya.